A cohort study of the recovery of health and wellbeing following colorectal cancer (CREW study): protocol paper - Fenlon Deborah; Richardson Alison; Addington-Hall Julia; Smith Peter; Corner Jessica; Winter Jane; Foster Claire (BMC, 2012)
Abstract Background The number of people surviving colorectal cancer has doubled in recent years. While much of the literature suggests that most people return to near pre-diagnosis status following surgery for colorectal cancer, this literature has largely focused on physical side effects. Longitudinal studies in colorectal cancer have either been small scale or taken a narrow focus on recovery after surgery. There is a need for a comprehensive, long-term study exploring all aspects of health and wellbeing in colorectal cancer patients. The aim of this study is to establish the natural history of health and wellbeing in people who have been treated for colorectal cancer. People have different dispositions, supports and resources, likely resulting in individual differences in restoration of health and wellbeing. The protocol described in this paper is of a study which will identify who is most at risk of problems, assess how quickly people return to a state of subjective health and wellbeing, and will measure factors which influence the course of recovery. Methods/design This is a prospective, longitudinal cohort study following 1000 people with colorectal cancer over a period of two years, recruiting from 30 NHS cancer treatment centres across the UK. Questionnaires will be administered prior to surgery, and 3, 9, 15 and 24 months after surgery, with the potential to return to this cohort to explore on-going issues related to recovery after cancer. Discussion Outcomes will help inform health care providers about what helps or hinders rapid and effective recovery from cancer, and identify areas for intervention development to aid this process. Once established the cohort can be followed up for longer periods and be approached to participate in related projects as appropriate and subject to funding.